2019
DOI: 10.1002/mgg3.958
|View full text |Cite
|
Sign up to set email alerts
|

Association between APOE polymorphisms and lipid profile in Mexican Amerindian population

Abstract: BackgroundApolipoprotein E (ApoE) is a glycoprotein that plays an important role in lipid homeostasis at both cerebral and systemic levels. Moreover, the differential distribution of APOE gene alleles among different populations, means that ApoE isoforms could have different effects on lipids metabolism. The present study aims to evaluate the relationship between APOE gene alleles and the lipid profile in a Mexican Amerindian (MA) population.MethodsThis study included 1997 MA individuals of different ethniciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
4
11
1
Order By: Relevance
“…The mechanism may be that APOE E2 can bind to low-density lipoprotein receptor (LDLR) by cysteine at amino acid position 158, which will affect the up-regulation of the synthesis of LDLR and 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA), resulting in low serum LDL levels ( Lee et al, 2011 ). Previous studies showed that APOE E4 was associated with higher LDL levels ( Martínez-Magaña et al, 2019 ; Wang et al, 2019 ); however, in the present study, we did not find such a relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…The mechanism may be that APOE E2 can bind to low-density lipoprotein receptor (LDLR) by cysteine at amino acid position 158, which will affect the up-regulation of the synthesis of LDLR and 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA), resulting in low serum LDL levels ( Lee et al, 2011 ). Previous studies showed that APOE E4 was associated with higher LDL levels ( Martínez-Magaña et al, 2019 ; Wang et al, 2019 ); however, in the present study, we did not find such a relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with the findings reported by several studies indicating decreased plasma and APOE gene expression in MS patients (11,12). It is reported that some studies indicated a positive association between ApoE gene polymorphism and the risk of MS progression whereas other studies generated negative results (5,(13)(14)(15)(16)(17). However, the results remain controversial.…”
Section: Discussionsupporting
confidence: 90%
“…It is reported that some studies indicated a positive association between ApoE gene polymorphism and the risk of MS progression whereas other studies generated negative results (5,(13)(14)(15)(16)(17). However, the results remain controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in other lipid metabolism‐related genes based on population genetic differences may influence differences in lipid spectrum regulation 29‐31 . In addition, one factor that may modulate the relationship between APOE gene variations and lipid levels is body mass index (BMI) 32 . BMI information was not collected and analyzed, which was one of the shortcomings of this study.…”
Section: Discussionmentioning
confidence: 99%